Властивостi позаклiтинної фруктозо-1,6-бiсфосфатази Вacillus subtilis - Ястребова, О.В.; Панченко, Л.П.; Скрипаль, I. Г. (Видавничий дім "Академперіодика" НАН України, 2008)
Extracellular fructose bisphosphatase (FBFase) (EC 3.1.3.11) from spore-forming bacterium Bacillus subtilis is obtained. The enzyme is inactivated in the absence of Mg2+ or Mn2+. Maximum activity of the enzyme is observed with substrate at the 2mM concentration. AMP inhibits FBFase activity, but the presence of PEP reduces this effect. Heavy metal ions at a concentration of 0.1 mM in the presence of Mg2+ are not inhibitors. Effect of Zn2+ ions on the enzyme activity is different depending on pH and the presence of Mg2+ and EDTA. Monovalent cations are insignificant effectors of extracellular FBFase only at their low concentrations. The subunit size determined by SDS-PAGE analysis was 63 kDa, which was confirmed by gelfiltration (230 kDa).